Musical Neglect Training for Chronic Persistent Unilateral Visual Neglect Post-stroke - Kang, Kyurim; Thaut, Michael H. (Frontiers in Neurology, 2019)
Unilateral visual neglect from right hemispheric stroke is a condition that reduces a person’s ability to attend to and process stimuli in their left visual field, resulting in neglect and inattention to the left side of their environment. This perceptual processing deficit can negatively affect individuals’ daily living which in turn reduces functional independence. Musical Neglect Training (MNT) has been developed based on previous research evidence to improve left visual field processing. Two individuals with persistent chronic unilateral visual neglect participated in this study. Participants underwent six individual MNT sessions. Active MNT was used involving exercises on musical equipment (tone bars) to complete musical patterns emphasizing attentional focus towards the neglect visual field. Two standardized assessments (Albert’s and Line Bisection Test) were used. The assessments were administered immediately before and after each of the 6 MNT sessions to assess the within-session effect of MNT. Follow-up testing was done one week after their 6th session to examine the longer-lasting effects of MNT. Paired t-test and Wilcoxon signed rank test were used to examine results. Both participants showed significant improvement pre vs. posttest on the Albert’s Test but not on the Line Bisection Test. The current study presents the positive potential of MNT for patients with chronic persistent visual neglect. In particular, effects were shown for exploratory visuomotor neglect (Albert’s test), but not for egocentric perceptive neglect (Line Bisection Test), and substantiated for within-session effects only. The predictable auditory stimulus patterns associated with object sequences (tone bars) to provide feedback, direct spatial attention and orientation, and initiate intention for movement into the neglect field may offer specific advantages to reduce persistent perceptual attention deficits.